Temporal Characteristics of the Oropharyngeal and Nasal Microbiota Structure in Crewmembers Stayed 180 Days in the Controlled Ecological Life Support System - Chen, Yanwu; Xu, Chong; Zhong, Chongfa; Lyu, Zhitang; Liu, Junlian; Chen, Zhanghuang; Dun, Huanhuan; Xin, Bingmu; Xie, Qiong (Frontiers in Microbiology, 2021)
During the long-term space flight, the control of harmful microorganisms is very important. Confined experiments are carried out to simulate the closed environment of space capsule on the ground to study the characteristics of microbial dynamics changes, so as to provide reference for the prevention of human pathogenic infection in space. The Chinese CELSS (Controlled Ecological Life Support System) is unique in design including a closed-loop system supporting 4 healthy volunteers surviving for 180 days. We investigate the distribution of microorganisms and their dynamic characteristics in the nasal cavity and oropharynx of occupants with prolonged confinement. Based on 16S rDNA v3-v4 region using Illumina high-throughput sequencing technology, the oropharyngeal and nasal flora were monitored at 8 time points during confinement. There were significant differences between oropharyngeal and nasal flora, and there were also individual differences among the same sites of different volunteers. Analysis on the structure of the bacterial flora showed that, in the phylum taxon, the nasal bacteria mainly belonged to Actinobacteria, Firmicutes, Proteobacteria and Bacteroidetes, etc. In addition to the above phylums, in oropharyngeal bacteria Fusobacterial accounted for a relatively high proportion. In the genus taxon, the nasal and oropharyngeal bacteria were independent, and Corynebacterium and Staphylococcus were dominant in nasal cavity, and Corynebacterium, Streptococcus and Neisseria were dominant in oropharynx. With the extension of the confinement time, the number of Staphylococcus in the nasal cavity and Neisseria in the oropharynx increased, and the diversity index Chao fluctuated greatly from 30 days to 90 days after the volunteers entered the CELSS. Conclusion: The structure and diversity of the nasal cavity and oropharyngeal flora changed in the CELSS, and there was the phenomenon of migration between occupants, suggesting that the bacterial flora structure and health of the respiratory tract could be affected by living in a closed environment for a long time.